Community of practice and green learning. The case of a Permaculture Art Cooperative - Martin, Rocío Belén (2020)
This paper addresses the issue of communities of practice in an art and permaculture cooperative. The contributions of the situated theory of learning, the Social Economy and Permaculture, allowed to think of the cooperatives as spaces of social-community interactionsthat promote education and learning for the sustainability of life. In this context, the practice, cooperation and participation acquired transcendence for the co-construction of identities and for a shared development of mastery, interests and trajectories. The case study aimed to learn about relevant aspects of learning that contributed to understanding the emergence, development and consolidation of a cooperative understood as a community of practice; interviews were conducted with members of the art and permaculture cooperative "Reciclando Utopías", with its eco-productive headquarters, located in Rio Ceballos, Cordoba, Argentina. The organization develops its activities respecting the characteristics of the natural ecosystem, sustainable design, agriculture and permanent culture. In-depth interviews were conducted with four people who develop services in the cooperative. The analysis of the data made it possible to learn about the forms of participation, aspects related to the emergence and continuity of the cooperative as a community of practices, trajectories, identity and commitment, green learning and cooperativism. In this sense, within the cooperative it was possible to recognize a diversity of learning trajectories in the cooperation practices andin the process of permanent and continuous green learning of permaculture.